EFEKTIVITAS STRUKTUR ORGANISASI BAPPEDA KABUPATEN KUTAI KARTANEGARA DALAM KEDUDUKANNYA SEBAGAI PERANGKAT DAERAH BERDASARKAN PERATURAN PEMERINTAH NOMOR 18 TAHUN 2016 - Halim Hamilton; Hartutiningsih Hartutiningsih; Adri Patton (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This article will review the organizational structure's effectiveness through the complexity, formalization, and centralization of BAPPEDA Kutai Kartanegara Regency in its position as a regional apparatus based on Government Regulation Number 18 of 2016. With a qualitative approach and interactive data analysis, the research findings show that the BAPPEDA organizational structure's effectiveness in Kutai Regency Kartanegara is quite effective and follows existing regulations. It can be seen from the achievement of the targets that have been set.Keywords: Effectiveness, Organizational Structure, Complexity, Formalization, Centralization